Cognitive behavioural therapy for the treatment of chronic fatigue syndrome in adults – a meta-analysis - Kolala, Vivek; La Rosa, Billie; Vangaveti, Venkat; Chen, Kai Yang (Frontiers in Psychiatry, 2025)
The treatment efficacy of Cognitive Behavioural Therapy (CBT) for chronic fatigue syndrome (CFS) remains controversial. The purpose of this meta-analysis was to understand the short-term and long-term efficacy of CBT on different outcome measures on patients with CFS, as well as explore potential adverse effects. A meta-analysis was conducted in accordance with PRISMA 2020 guidelines (PROSPERO: CRD42023391926). PubMed, PsycINFO, CINAHL, SCOPUS, Web of Science, and EMBASE were searched from inception to September 2024 for randomised controlled trials (RCTs) of CBT in adults with CFS excluding Oxford-defined cohorts. Interventions included individual face-to-face, self-directed, and group CBT. The primary outcome was fatigue, with secondary outcomes of physical functioning, anxiety, depression, pain and quality of life. Risk of bias was assessed using the Cochrane Risk of Bias 2.0 tool. There were 12 studies included in this review, with 1799 total participants. All forms of CBT, when analysed together, was not found to have a statistically significant result (p = 0.12). Individual face-to-face CBT was found to have a large effect size in reducing fatigue (Cohen's d = 2.91, 95% CI 0.51 to 5.31, p=0.02). Self-directed CBT was found to have a large effect size in improving physical functioning (Cohen's d = -2.76, 95% CI -5.06 to -0.47, p=0.04). All other sub-analyses did not yield statistically significant results. There was inconsistent reporting of adverse effects, however no serious adverse effects were reported. High heterogeneity and incomplete reporting limit certainty. CBT as a treatment modality inherently leads to difficulties with blinding and bias. The results suggest that patients with milder disease may benefit more from self-directed CBT. Group CBT may not be as beneficial as other modalities. Guidelines provide mixed recommendations regarding CBT, therefore CBT may be offered as a supportive, non-curative option for adults with CFS. No funding was received for this review.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023391926.